MCP-PMT studies at the High-B test facility at Jefferson Lab. (30th March 2016) - Ilieva, Y.; Allison, L.; Cao, T.; Kalicy, G.; Nadel-Turonski, P.; Park, K.; Schwarz, C.; Schwiening, J.; Zorn, C.
Abstract: Here we present preliminary results for the gain performance of commercially available 3- μ m and 6- μ m pore-size single-anode microchannel-plate photomultipliers (MCP PMTs) in magnetic fields up to 5 T and for various orientations of the sensor relative to the field direction. The measurements were performed at Thomas Jefferson National Accelerator Facility in Newport News, VA. Our results show that smaller-pore-size PMTs have better gain performance in magnetic fields. At various angles, the shape of the gain dependence on the strength of the magnetic field strongly depends on the type of the sensor. Also, for each sensor, the azimuthal dependence is strongly correlated with the polar angle. Overall, the sensors exhibit a reasonable performance up to 2 T, although that upper limit depends on the sensor, the applied high voltage, and the orientation of the sensor relative to the field. To optimize the operational and design parameters of MCP PMTs for performance in high magnetic fields, further measurements and simulation studies will be pursued. Our studies are part of an R&D for development of a Detector of Internally Reflected Cherenkov Light for the central detector of a future U.S. Electron Ion Collider.